Rheological Properties and Crosslinking Rheo-Kinetics of CMHEC/CTAB Synergistic Systems. Issue 12 (1st December 2016) - Li, Guodong; Fang, Bo; Lu, Yongjun; Li, Kejing; Ma, Ming; Yang, Mo; Qiu, Xiaohui; Wang, Liwei; Liu, Yuting
Abstract : Aiming at synergistic interaction between carboxymethyl hydroxyethyl cellulose (CMHEC) and cetyltrimethyl ammonium bromide (CTAB), mixtures of CMHEC and CTAB solutions were investigated, employing relative viscosity and rheological measurements. The effects of mass ratio of CMHEC and CTAB solutions, temperature, and polysaccharide concentration on relative viscosities of CMHEC/CTAB systems were studied. Rheological method was used to study rheo-kinetics of the isothermal crosslinking process for CMHEC/CTAB synergistic fracturing fluid, and the novel crosslinking rheo-kinetics equation was established. The results showed the strong synergism between CMHEC and CTAB, resulting in a higher relative viscosity, storage modulus G ′, and loss modulus G ″ than that of separate ones. CMHEC/CTAB systems behave as pseudoplastic fluids with considerable thixotropy and viscoelasticity, and the flow behavior can be well described by Carreau−Williamson model. The crosslinking rheo-kinetics equation can well describe the isothermal crosslinking process at different shear rates. The model parameters are well-defined and reasonable. GRAPHICAL ABSTRACT: